Development of TikTok-based Chemo-entrepreneurship e-Worksheet to Fostering Students’ Entrepreneurial Spirit - Fitriyani, Riyan; Suprihatiningrum, Jamil (Jurnal Paedagogy, 2024)
This research aims to develop an e-worksheet and analyze its quality based on the assessment of material experts, media experts, and chemistry teachers, as well as knowing students’ responses to TikTok-based chemo-entrepreneurship e-worksheet products. The method used a 4D model consisting of define, design, development, and disseminate stages, but was limited to the developing stage. Data collection techniques in this research were interviews, validation sheets, and student response questionnaires. The data obtained was analyzed qualitatively and quantitatively. The result of this study indicated that the e-worksheet product was rated very good (with an ideal percentage of 90%) by material experts, very good (with an ideal percentage of 97% by media experts, and very good (with an ideal percentage 96%) by the reviewer. Students responded very well to the e-worksheet product (with an ideal percentage of 96%). Thus, the TikTok-based Chemo-entrepreneurship e-worksheet can be used as an alternative chemistry learning medium while developing the participants’ entrepreneurial spirit.